How does bridging social capital relate to health-behavior, overweight and obesity among low and high educated groups? A cross-sectional analysis of GLOBE-2014 - Carlijn B. M. Kamphuis; Joost Oude Groeniger; Maartje P. Poelman; Mariëlle A. Beenackers; Frank J. van Lenthe (BMC, 2019)
Abstract Background Social capital is an important determinant of health, but how specific sub-dimensions of social capital affect health and health-related behaviors is still unknown. To better understand its role for health inequalities, it is important to distinguish between bonding social capital (connections between homogenous network members; e.g. similar educational level) and bridging social capital (connections between heterogeneous network members). In this study, we test the hypotheses that, 1) among low educational groups, bridging social capital is positively associated with health-behavior, and negatively associated with overweight and obesity, and 2) among high educational groups, bridging social capital is negatively associated with health-behavior, and positively with overweight and obesity. Methods Cross-sectional data on educational level, health-behavior, overweight and obesity from participants (25-75 years; Eindhoven, the Netherlands) of the 2014-survey of the GLOBE study were used (N = 2702). Social capital ("How many of your close friends have the same educational level as you have?") was dichotomized as: bridging ('about half', 'some', or 'none of my friends'), or bonding ('all' or 'most of my friends'). Logistic regression models were used to study whether bridging social capital was related to health-related behaviors (e.g. smoking, food intake, physical activity), overweight and obesity, and whether these associations differed between low and high educational groups. Results Among low educated, having bridging social capital (i.e. friends with a higher educational level) reduced the likelihood to report overweight (OR 0.73, 95% CI 0.52-1.03) and obesity (OR 0.58, 95% CI 0.38-0.88), compared to low educated with bonding social capital. In contrast, among high educated, having bridging social capital (i.e. friends with a lower educational level) increased the likelihood to report daily smoking (OR 2.11, 95% CI 1.37-3.27), no leisure time cycling (OR 1.55, 95% CI 1.17-2.04), not meeting recommendations for vegetable intake (OR 2.09, 95% CI 1.50-2.91), and high meat intake (OR 1.39, 95% CI 1.05-1.83), compared to high educated with bonding social capital. Conclusions Bridging social capital had differential relations with health-behavior among low and high educational groups. Policies aimed at reducing segregation between educational groups may reduce inequalities in overweight, obesity and unhealthy behaviors.